Popular artistic expression in Lima: From the chicha poster to the chicha aesthetic - Quispe Lázaro, Arturo (2021)
This article examines the initial points of a creative process that articulates new popular identities in Lima that comes from the economic and cultural circuit of chicha music. These are symbolically expressed in the graphic production called chicha aesthetics, which since the second decade of this century has been positioned with new vigor in the capital. Chicha aesthetics is a diversity of graphic, artistic and cultural productions that emerged approximately in 2010, it had its origin in the classic chicha poster that has been published on the walls of neighborhood houses in Lima since the 1970s. In the article we will focus on pointing out the process that gave rise to the new graphic proposals, the transition from a creative process anchored to chicha musical expression to another that, starting from it, discovers another type of sensitivity linked to graphic art, of a generation that It was nourished by chicha music and today it expresses itself with its own voice and sensitivity, giving a turn to the cultural productions of the last century. All this originated a diversity of artistic creations, it expanded in the city and they called it chicha aesthetics.